Analysis and practice of tax risks in foreign economic activity of developed foreign countries (Eurasian Research Bulletin, 2024)
As globalization continues to shape the landscape of international trade, the foreign economic activity of developed countries faces an array of tax-related challenges. This abstract explores the analysis and practical experiences of tax risks in the context of foreign economic endeavors undertaken by developed nations. The paper investigates the diverse tax risks that emerge when businesses engage in cross-border transactions and assesses how developed countries navigate these challenges. Drawing on empirical data and case studies, it analyzes the strategies and mechanisms employed by these countries to manage tax risks effectively. Key areas of focus include the impact of international tax frameworks, transfer pricing complexities, and evolving regulatory landscapes on tax risks in foreign economic activities. The paper also examines the role of technology in tax risk management, considering how digitalization and data analytics are reshaping compliance efforts and risk mitigation strategies. By synthesizing theoretical insights with practical experiences, this abstract aims to contribute to the understanding of tax risk management in the foreign economic activities of developed countries. It provides valuable insights for policymakers, tax professionals, and businesses operating in the global arena, fostering a more informed and proactive approach to navigating the complex terrain of international taxation